Enhancing public information quality during the Covid-19 pandemic: A cyber public relations strategy on local government initiatives - Nihayah, Silvia Salma Ainun; Afifi, Subhan (Communications in Humanities and Social Sciences, 2023)
The Covid-19 pandemic has induced widespread fear, emphasizing the imperative for high-quality public information dissemination to alleviate societal anxiety. This research examined the Cyber Public Relations (Cyber PR) strategies implemented by the Communication and Informatics Office or Dinas Komunikasi dan Informatika (Diskominfo) of Jepara Regency in disseminating quality public information during the ongoing pandemic. Utilizing a qualitative case study methodology, the study focused on the efforts of Diskominfo Jepara to enhance public information quality, specifically related to Covid-19 data updates, health protocol campaigns, and the Covid-19 vaccination campaign. Data collection involved in-depth interviews, observations, and documentation. The analysis employed the Cyber PR framework, assessing dimensions such as strategic, integrated, targeted, and measurable, alongside indicators like intrinsic, contextual, representational, and accessibility for scrutinizing public information quality. Findings revealed some key elements in Diskominfo Jepara's Cyber PR strategies, including the establishment of a comprehensive digital media center, active engagement with media outlets, collaborations with influencers, and the utilization of Key Opinion Leaders (KOLs). These strategies have been intricately developed based on situational analysis and predefined communication objectives. The research contributes significantly to the academic literature on Cyber PR in local government contexts, providing nuanced insights and enriching the reference landscape.